Effect of fiber treatment on flexural properties of natural fiber reinforced composites: A review - Mohit Sood; Gaurav Dwivedi (Egyptian Journal of Petroleum)
Fiber treatments and coupling agents have been applied by composites researchers to improve the functionality in the flexural loading of natural fiber reinforced composites. This paper reviews how fiber treatments upshot to flexural strength and modulus of natural fiber composites during 2000–2016. Chemical treatments improved fiber interface bonding with matrix and impart more strengths to composites. Coupling agents also ameliorate flexural properties and the combination of treatments is equally supercilious. The negative impact of fiber’s physical treatments on flexural properties of natural fiber composites also reviewed. Eventually, a number of perspectives have been concluded with the hope that our work will succor to further betterment in flexural strength of natural fiber composites. Keywords: Natural fibers, NaOH, Matrix, Coupling agent, Composites